Downton Abbey. Season 5 [videorecording (Blu-Ray)] - Fellowes, Julian; Smith, Maggie, 1934-2024; McGovern, Elizabeth, 1961-; Bonneville, Hugh; Dockery, Michelle, 1981-; Carter, Jim, 1948-; Cassidy, Raquel, 1968-; Coyle, Brendan; James-Collier, Rob; Leech, Allen; Logan, Phyllis; McShera, Sophie; et al. (PBS Distribution, 2014)
Season five of the international hit finds the Crawley family and the staff struggling with responsibilities and choices as they adjust to life in the Roaring Twenties.